Index of destination attractiveness: a quantitative approach for measuring tourism attractiveness - ISLAM, NASER UL; Chaudhary, Manjula (Turizam, 2020)
The common perceptions about tourist destinations often hold even in the absence of facts and evidences. This research is an attempt to analyze the ground behind generic perceptions about tourism attractiveness of Kashmir valley. This has been done through primary survey of most important stakeholders; the visiting tourists. The data collected from 370 tourists has been used to deconstruct tourism attractiveness into different parameters and an Index of destination attractiveness has been prepared to understand the importance of each parameter to overall attractiveness. The evidences support the common perception that natural attractions play very important role in tourism attractiveness of valley but valley lacks other tourism motivators and falls short on most of the hygiene factors. These findings can be used to increase the attractiveness of valley by working on weak areas and the Index developed for the study can be used as a standard tool for continuous monitoring of attractiveness.